Rebranding austriackiej chadecji - analiza manifestów wyborczych Nowej Partii Ludowej = Rebranding the Austrian Christian Democrats - analysing election manifestos of the New People's Party - Miecznikowska, Justyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper also attempts to pinpoint the deciding factors involved in the success of the Austrian Christian Democrats as measured by the party's victory in the 2017-2019 National Council elections and being granted a mandate to form the federal government twice. The adopted hypothesis is that the Austrian Christian Democrats may attribute their electoral victory to cohesive and effective rebranding - an image rejuvenation achieved by replacing the party leader, changing the style of making politics, and revising its political platform. The New People's Party owes its triumph to a successful absorption of topics that, until recently, have been identified with the far-right only.
Keywords: Nowa Partia Ludowa; Austria; Kurz, Sebastian (austriacki polityk; 1986- ); chadecja; manifest wyborczy; New People's Party; Christian democrats; election manifesto